Zoonotic Diseases: A Changing Landscape Demands Global Action - Naithani, Priyanka; Bahurupi, Yogesh; Singh, Meenu (Indian Journal of Community Health, 2024)
During recent years, the globe-wide zoonotic disease landscape has evolved drastically posing significant challenges to the health of the individual and environmental sustainability. Zoonotic illnesses, which occur in animals and are transmission-capable to people, have been an ever-present risk throughout history. According to the “World Health Organization (WHO)”, an estimated 60% of known infectious diseases and around 75% of new or emerging infectious diseases are zoonotic in origin. These illnesses have the potential to inflict widespread morbidity and mortality, along with severe economic losses. However, today's dynamics of our changing environment, which include urbanization, climate change, and growing human-animal interaction, are increasing the probability of zoonotic spillover occurrences. (1) The worldwide spread of the consequences of zoonotic illnesses underscores the critical need for collective effort through international leadership frameworks integrating government, private industry, and civil society. “The Global Health Security Agenda (GHSA)” and the WHO are collaborating on projects to address these concerns and improve global health security. The WHO launched the "One Health Joint Plan of Action," which intends to inscribe health hazards to humans, animals, plants, and the environment. It emphasizes the interconnection of human, animal, and environmental health. (2)